PENGEMBANGAN BUKU AJAR KIMIA SMA/MA KELAS XI SEMESTER II DALAM UPAYA MENINGKATKAN HASIL BELAJAR DAN MENUMBUHKEMBANGKAN KARAKTER SISWA - Mahmud Mahmud; Ajat Sudrajat; Shofia Rija Napitupulu (Jurnal Pendidikan Kimia (JPKim), 2015)
AbstractThis study aims to develop of chemistry textbooks that used in Eleventh Grade of Senior high school of second semester based on 2013 curriculum to improve students’ achievement and develop students’ character. The samples of this study are SMAN 1 Lubuk Pakam, SMAN 2 Lubuk Pakam, Nusantara Senior High School, MAN Lubuk Pakam. The sample treatment is divided into two, experimental class and control class. The Data collection is done with objective tests, observation sheets during the learning process is done as well as a questionnaire to measure the evolving character at the end of learning. Data were analyzed using SPSS 19 with significance level 0.05. To determine difference in students’ achievement and students’ character by using Cooperative problem Based Learning. The effectiveness score of textbooks quality was 84.37 and KTSP textbook was 74.41. In addition, this research improves students’ achievement and character such as responsibility, creative, communicative and psychomotor. The students’gain achievement of the experiment class was 74.92 and the control class was 67.11. The effectiveness score of communicative character in experiments class was 78,08 and the controll class was 74.26, the creative character in experiment class was 78.28 and the controll class was 75.12, and the responsibility character in experiment class was 79.51 and the controll class was 75.30. The results of this study of indicate that the chemistry textbook was develop in this study can to to improve students’ Achievement and develop students’ character.Kata Kunci : Buku Ajar Kimia, Cooperative Problem Based Learning, Hasil Belajar, Tanggung Jawab, Kreativitas, Komunikatif, Psikomotorik